TACE, DEE-TACE, and Its Evolution in Metastatic Disease - Byers, Luke; Brown, Matthew A.; Johnson, D. T.; Rochon, Paul J. (Digestive Disease Interventions, 2019)
Intra-arterial hepatic therapy is a relatively new technique popularized in the 1990s and 2000s and is built on decades of incremental development and discovery. Intra-arterial oncologic embolization therapy broadly includes transarterial embolization, transarterial chemoembolization (TACE), drug-eluting embolic transarterial chemoembolization, and transarterial radioembolization. These therapies have been included in the multidisciplinary treatment algorithm of hepatocellular carcinoma (HCC) and metastatic disease. Barcelona Clinic for Liver Cancer treatment guidelines specifically recommends TACE for the treatment of intermediate stage HCC. Research and clinical practice have seen extension of intra-arterial therapy to also broadly include unresectable HCC in many circumstances including palliation and a bridge to transplant. Some evidence also suggests an expanding role for intra-arterial therapy in the context of other primary liver neoplasms as well as metastatic disease with general considerations carrying over from the experience of treating HCC. In general, the efficacy of these treatments is similar, and selection of therapy is based on physician expertise and preference.
Keywords: transarterial chemoembolization and radioembolization; hepatocellular carcinoma; metastatic disease